2013
DOI: 10.1038/nchembio.1183
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical activation of TRPA1 channels in neurons and animals

Abstract: Optogenetics is a powerful research tool because it enables high-resolution optical control of neuronal activity. However, current optogenetic approaches are limited to transgenic systems expressing microbial opsins and other exogenous photoreceptors. Here, we identify optovin, a small molecule that enables repeated photoactivation of motor behaviors in wild type animals. Surprisingly, optovin's behavioral effects are not visually mediated. Rather, photodetection is performed by sensory neurons expressing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 47 publications
2
120
0
4
Order By: Relevance
“…We previously showed that aspirin, unlike ibuprofen, can block the ability for opioids to reduce myocardial reperfusion injury. 30 Although more studies are needed, potentially other myocardial salvaging techniques (such as using volatile anesthetics 31 or implementing remote conditioning 31 ) may also have a reduced efficacy for limiting myocardial ischemia-reperfusion injury when TRPA1 is inhibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that aspirin, unlike ibuprofen, can block the ability for opioids to reduce myocardial reperfusion injury. 30 Although more studies are needed, potentially other myocardial salvaging techniques (such as using volatile anesthetics 31 or implementing remote conditioning 31 ) may also have a reduced efficacy for limiting myocardial ischemia-reperfusion injury when TRPA1 is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…32 For our study, the binding site for optovin is identified to be within a region of critical cysteines present on TRPA1 that is also essential for reactive aldehyde-induced TRPA1 activation. 12, 31 Although further studies will be needed, the TRPA1 activators we used may reduce injury during a heart attack by occupying critical cysteines of TRPA1; limiting the amount of irreversible reactions which occur by reactive aldehydes during the initial minutes of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a small molecule known as optovin was shown to serve as a photochromic activator of TRPA1 channels, enabling optical control of behavior in zebrafish 23 (Table 1). …”
Section: Controlling Native Ion Channels With Photochromic Ligandsmentioning
confidence: 99%
“…However, thus far vertebrate in vivo screenings for neuroactive or cardiotoxic molecules have been performed with zebrafish embryos. In these studies, compound treated animals were explored by using fully automated systems and/or specialized software for alterations of behavioral patterns [15][16][17] or cardiac activity [18,19]. One of the major obstacles performing such investigations with Xenopus tadpoles is the lack of simple and effective high-throughput screening methodologies.…”
Section: Introductionmentioning
confidence: 99%